On Spirallike Functions Related to Bounded Radius Rotation - ÇETİNKAYA, ASENA; Taştan, Hakan Mete (The Honam Mathematical Society (호남수학회), 2022)
In the present paper, we prove the growth and distortion theorems for the spirallike functions class S-k(lambda) related to boundary radius rotation, and by using the distortion result, we get an estimate for the Gaussian curvature of a minimal surface lifted by a harmonic function whose analytic part belongs to the class S-k (lambda). Moreover, we determine and draw the minimal surface corresponding to the harmonic Koebe function.
Keywords: Bounded Radius Rotation; Spirallike Function; Minimal Surface